User Interface Design With User Centered Design (UCD) Method on Bread Sales Mobile Application PT.Nippon Indosari Corpindo, Tbk - Salsa Salsa Az-zahra; Irsan Jaelani; Lise Sri Andar Muni (Institut Pendidikan Indonesia, 2021)
PT. Nippon Indosari Corpindo,Tbk. is one of the companies engaged in the food industry with its flagship product, namely bread with the brand